Analisis Produk dan Harga terhadap Keputusan Konsumen Sepatu Bola Merek Adidas (Studi Kasus: Konsumen pada Toko-Toko Olahraga di Kota Pangkalpinang, Provinsi Kepulauan Bangka Belitung) - Juhari - (Jurnal Bisnis Darmajaya, 2015)
In information technology era, there are so much promising chance and business challenge for enterprises in Indonesia, for instance to expand the market target of products from Indonesian enterprises. But, in other hand, this challenge also brings a tough competition. So that, the enterprise should have a good strategy to face the competition, but also focus on developing their business, products, price, promotion, and effectively distribute their products. One of developed business in Indonesia is sport product seller. The issue of this paper is how to analyze the products and price toward consumer decision to buy sport shoes brand Adidas at sport shop in Pangkalpinang city. Based on the result of double regression analysis partially and simultaneously, there is significant and positive effect between product (x1) and price (x2) toward consumer decision in selecting soccer shoes brand Adidas at sport shop in Pangkalpinang city. The regression equation between each variable is Y= 0,117 + 0,827X1 + 0,168 X2 + e or determination coefficient value of 0.787 (73.8%) that means 73.8% decision variable can be explain by variable product and price.Key words –product, price, consumer decision